Zoonotic intestinal parasites and vector-borne pathogens in Italian shelter and kennel dogs. (April 2017) - Traversa, Donato; Di Cesare, Angela; Simonato, Giulia; Cassini, Rudi; Merola, Carmine; Diakou, Anastasia; Halos, Lénaïg; Beugnet, Frederic; Frangipane di Regalbono, Antonio
Highlights: Dogs from kennels and shelters from Italy have been included in the study. The presence of zoonotic parasites and vector-borne pathogens has been investigated. Mono-specific and poli-specific positivity has been recorded. Improved control measures are crucial to minimize the risk of infection for people and dogs. Abstract: This study investigated the presence of zoonotic parasites and vector-borne pathogens in dogs housed in kennels and shelters from four sites of Italy. A total of 150 adoptable dogs was examined with different microscopic, serological and molecular methods. Overall 129 dogs (86%) were positive for one or more parasites and/or pathogens transmitted by ectoparasites. Forty-eight (32%) were positive for one infection, while 81 (54%) for more than one pathogen. The most common zoonotic helminths recorded were hookworms, roundworms and Capillaria aerophila, followed by mosquito-borne Dirofilaria spp. and Dipylidium caninum . One hundred and thirteen (77.9%), 6 (4.1%) and 2 (1.4%) dogs were positive for Rickettsia spp., Leishmania infantum and Anaplasma spp., respectively. The results show that dogs living in rescue facilities from the studied areas may be infected by many zoonotic internal parasites and vector-borne pathogens, and that control measures should be implemented.